Potassium fixation by oxidized and reduced forms of different phyllosilicates - Tran, Angela M. (Kansas State University, 2012)
Factors governing potassium fixation and release are poorly understood. This study was conducted to investigate the effects of clay mineralogy and structural iron oxidation state on potassium fixation. Five reference clays and two soil clays were used to capture a range in mineralogical compositions and potassium behaviors. Reference clays used were illite (IMt-1), kaolinite (KGa-1b), montmorillonite (STx-1b), nontronite (NAu-2), and vermiculite (VTx-1). Soil clays used were from the upper 15 cm of a Belvue loam (BEL) and a Cherokee silt (CHE). Potassium fixation capacities were measured on unaltered as well as sodium dithionite reduced forms of each clay. Ferrous and total iron contents were determined photometrically using 1, 10-phenanthroline. Potassium fixation was measured by potassium saturating the clays and washing off exchangeable and solution potassium with solutions of magnesium chloride; samples were then acid digested and the amount fixed was calculated as the amount of potassium in the acid digestion minus the amount originally in the sample. BEL released potassium rather than fixed it while CHE tended to release potassium in the unaltered form and fix potassium in the reduced form. Structural iron reduction significantly impacted the amounts of potassium fixed by VTx-1 and NAu-2, which had the highest total iron contents of all the clays evaluated. NAu-2 and VTx-1 both on average fixed less than 1 mg K g clay[superscript]-1 in the unaltered form and an average of 6 and 11 mg K g clay[superscript]-1, respectively, in the reduced form. Regardless of being in the unaltered or reduced form, KGa-1b fixed essentially no potassium and IMt-1 and STx-1b fixed intermediate amounts of potassium—2 to 4 mg K g clay[superscript]-1 on average. The effects of clay mineralogy and structural iron oxidation state on potassium fixation can largely be explained through an understanding of layer type, layer charge, and charge distribution. In order for potassium fixation to occur, interlayer sites need to be accessible and available. Generally, the greater the negative layer charge the greater the amounts of fixation, with tetrahedral layer charge favoring fixation more than octahedral layer charge, and layer charge being a function of structural iron oxidation state.
Keywords: Potassium fixation; Iron redox state; Clay mineralogy; Soil potassium; Layer charge; Charge location; Agronomy (0285); Mineralogy (0411); Soil Sciences (0481)